Effects of Group, Individual, and Home Exercise in Persons With Parkinson Disease: A Randomized Clinical Trial. Issue 4 (October 2015) - King, Laurie A.; Wilhelm, Jennifer; Chen, Yiyi; Blehm, Ron; Nutt, John; Chen, Zunqiu; Serdar, Andrea; Horak, Fay B.
Abstract : Background and Purpose: Comparative studies of exercise interventions for people with Parkinson disease (PD) rarely considered how one should deliver the intervention. The objective of this study was to compare the success of exercise when administered by (1) home exercise program, (2) individualized physical therapy, or (3) a group class. We examined if common comorbidities associated with PD impacted success of each intervention. Methods: Fifty-eight people (age = 63.9 ± 8 years) with PD participated. People were randomized into (1) home exercise program, (2) individual physical therapy, or (3) group class intervention. All arms were standardized and based on the Agility Boot Camp exercise program for PD, 3 times per week for 4 weeks. The primary outcome measure was the 7-item Physical Performance Test. Other measures of balance, gait, mobility, quality of life, balance confidence, depressions, apathy, self-efficacy and UPDRS-Motor, and activity of daily living scores were included. Results: Only the individual group significantly improved in the Physical Performance Test. The individual exercise showed the most improvements in functional and balance measures, whereas the group class showed the most improvements in gait. The home exercise program improved the least across all outcomes. Several factors effected success, particularly for the home group. Discussion and Conclusions: An unsupervised, home exercise program is the least effective way to deliver exercise to people with PD, and individual and group exercises have differing benefits. Furthermore, people with PD who also have other comorbidities did better in a program directly supervised by a physical therapist. Video Abstract available for additional insights from the authors (see Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A112 ). Abstract : Supplemental Digital Content is Available in the Text.